2012
DOI: 10.3354/meps09907
|View full text |Cite
|
Sign up to set email alerts
|

Calanipeda aquaedulcis and Arctodiaptomus salinus are exceptionally euryhaline osmoconformers: evidence from mortality, oxygen consumption, and mass density patterns

Abstract: Mortality, respiration rate, and body mass density of the estuarine copepods Calanipeda aquaedulcis and Arctodiaptomus salinus and their eggs were studied over a wide range of salinities. Empirical hydrodynamic modeling was applied to calculate body mass density using the sinking speed of the copepods. According to the index of median lethal salinity (LS 50 ), the salinity tolerance ranges of C. aquaedulcis and A. salinus reared at 18 psu were 0.1 to 50 and 0.1 to 35 psu, respectively. No significant effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…Freitas et al, 2015;Shumway and Davenport, 1977), crustaceans (e.g. McAllen et al, 1998;Svetlichny et al, 2012) and echinoderms (e.g. Castellano et al, 2016a,b).…”
Section: Osmoregulatory Strategies Osmoconformersmentioning
confidence: 99%
See 1 more Smart Citation
“…Freitas et al, 2015;Shumway and Davenport, 1977), crustaceans (e.g. McAllen et al, 1998;Svetlichny et al, 2012) and echinoderms (e.g. Castellano et al, 2016a,b).…”
Section: Osmoregulatory Strategies Osmoconformersmentioning
confidence: 99%
“…Some authors have suggested that the increased energetic cost may be linked to increased activity (McAllen and Taylor, 2001) as the animal attempts to escape from unfavorable conditions (Gross, 1957). In other osmoconforming copepods, environmental salinity does not influence oxygen consumption rates (Svetlichny et al, 2012). However, most sources indicate that osmoconformers have low energetic requirements when exposed to decreased salinity.…”
Section: Stenohaline Speciesmentioning
confidence: 99%
“…In Sevastopol Bay minimum O. davisae number ranged between 1 (Almeda et al, 2011), where CDW = 0.0021 L 2.14 for nauplii, L is body length and CDW = 0.0318 L pr 1.61 for copepodites and females. (Svetlichny et al, 2012a), where ρb is equal to 1.05 g cm -3 (Svetlichny and Hubareva 2014), L, lpr and dpr are given in mm. and 400 ind m -3 when the water temperature was around 6-8ºC, and in Fukuyama Harbor it was recorded up to 5 x 10 3 ind m -3 when the surface temperature was around 10-13ºC.…”
Section: Discussion Life Cycle Of O Davisae In Sevastopol Baymentioning
confidence: 99%
“…Aquatic organisms with various salt tolerances adapt to their environments through osmoregulation and osmoconformation. Many copepods are osmoconformers (Bayly and Boxshall, 2009;Svetlichny et al, 2012).…”
Section: Table 1 Copepoda In Hypersaline Watersmentioning
confidence: 99%